2015
DOI: 10.1007/s10661-015-4482-x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury levels in avian feathers from different trophic levels of eight families collected from the northern region of Iran

Abstract: Mercury levels were determined in feathers from 83 birds belonging to 18 species (eight families), all collected from the northern region of Iran. Mercury levels were evaluated in relation to taxonomic affiliation and feeding strategies. Mercury levels in the feathers were between 0.05 ± 0.01 and 1.10 ± 0.15 μg g(-1) dry weight, and there was a significant effect of taxonomic groups (p < 0.05). The highest mercury levels were found in Accipitridae, and mercury was not detected in the family Upupidae. The patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Sublethal levels from 2.40 mg/kg have been shown to cause impairments in the reproductive processes (Scheuhammer et al 2007; Jackson et al 2011). Mashroofeh et al (2015) compared the Hg concentration in bird feathers from five different trophic levels, and their results show that the carnivore bird feathers (Hen harrier ( Circus cyaneus ): 0.80 ± 0.15 mg/kg; Marsh harrier ( C. aeruginosus ): 1.10 ± 0.20 mg/kg) accumulate more Hg, than piscivore, benthivore, omnivore or herbivore. Roque et al (2016) reported 1.4 mg/kg Hg in the primary feathers of Barn Owls.…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal levels from 2.40 mg/kg have been shown to cause impairments in the reproductive processes (Scheuhammer et al 2007; Jackson et al 2011). Mashroofeh et al (2015) compared the Hg concentration in bird feathers from five different trophic levels, and their results show that the carnivore bird feathers (Hen harrier ( Circus cyaneus ): 0.80 ± 0.15 mg/kg; Marsh harrier ( C. aeruginosus ): 1.10 ± 0.20 mg/kg) accumulate more Hg, than piscivore, benthivore, omnivore or herbivore. Roque et al (2016) reported 1.4 mg/kg Hg in the primary feathers of Barn Owls.…”
Section: Discussionmentioning
confidence: 99%
“…Several analytical techniques have been used to determine elemental concentrations in feathers such as flame, graphite furnace atomic absorption spectrometry (Markowski et al 2013), cold vapor atomic absorption spectrometry (CV-AAS) for Hg (Carvalho et al 2013;Carravieri et al 2014;Mashroofeh et al 2015), inductively coupled plasma optical emission (Szép et al 2003;Donovan et al 2006;Szép et al 2009) or inductively coupled plasma-mass spectrometry (ICP-MS) (Adout et al 2007;Norris et al 2007;Rubio et al 2016) and instrumental neutron activation analysis (Haskins et al 2011). All these techniques require sample digestion or dissolution prior to the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transfer from the environment into the animals in the area is a real possibility (Mashroofeh et al 2015). Hg levels in local bird species (e.g., Common hoopoe) may serve the image of this exposure.…”
Section: Introductionmentioning
confidence: 99%